The Physical Geography and Geology of Northeast Langkawi - Hussin, Azhar; Richard, Dorall,; H.H, Meor; S, Gokilan, (Malaysian Journal of Science, 2005)
The Northeast Langkawi is underlain by the Lower Paleozoic Setul Limestone Formation. Uplift and erosion of this sequence resulted in a karstic topography leaving a landform of limestones hills and mogote, caves, arches and sea stacks. The lower portions of the river basins, estuary, coasts and coral reefs constitute the NE Langkawi wetland complex. The infilling of the valley by sediments and later colonized by mangrove swamps and forest on the limestone hills imparted a contiguous mangrove and limestone forest landscape to that area. Steep rocky coasts of the limestones line most of the coast. White sandy beaches of quartzose sand and bioclastic grains are found on the bays facing open sea while muddy tidalflats dominate the protected coasts. In the offshore area, favouvarable conditions allowed coral reefs to grow and flourish. Unchecked development in the drainage basins let to increased sedimentation to this area and threatened the health of the ecosystem.